ONLINE PRICING FOR SMALL MEDIUM ENTERPRISES’ PRODUCTS IN THE EX-LOCALIZATION OF DOLLY SURABAYA - Ig. Jaka Mulyana; Ivan Gunawan; Dian Trihastuti; Yehezkiel Prakoso Putra Yunen; Dwi Agustin Nuriani Sirodj (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2021)
Numerous Small and Medium Enterprises (SMEs) do not have a basic method in pricing decisions. Many times, this decision comes up based on an intuitive probe instead of a detailed analysis. This could lead to marketing problems, which may result in disruptions of financial liquidity. This also applies to SMEs wishing to sell products through the online channel. They need a proper pricing strategy, considering its different marketing strategies. Sales made through both offline channels (conventional stores) and online channels are known as Dual-Channel Supply Chain (DCSC). It is argued that the pricing decision at DCSC needs to consider consumer preferences in selecting the sales channel. One assumption commonly adopted in the DCSC pricing model is that the lost value if consumers purchase products through online channels. Therefore, the pricing decision for the online channel should be cheaper than the price on the offline channel. This study aims to assist SMEs in the ex-localization of Dolly in Surabaya in determining the price of products to be sold through online channels. Three types of products: batik, chips, and leather shoes were selected as research samples to represent the product groups: craft, fashion, and processed food. This study proposes an optimal online price strategy through experiments with a mathematical model. Model parameters, namely consumer preferences in choosing sales channels, are obtained through surveys. Apart from that, surveys are also used to reveal which platforms consumers are interested in shopping online. Shopee and Instagram were chosen by respondents as the most popular marketplaces and social media for online shopping. Finally, the online prices proposed for the batik product are IDR 82,500-IDR 66,000; chips Rp7,620-Rp6,336; and leather shoes Rp.103,800-Rp82,200.